Exploring the intricacies of politeness and impoliteness in Acehnese speech variations - Taib, Rostina; Wardana, Muhammad Kiki; Safhida, Maya; Nurrahmah, Nurrahmah; Subhayni, Subhayni (Universitas Syiah Kuala, 2024)
This study examines politeness and impoliteness in Acehnese speech variations conveyed through various linguistic features, including honorifics, politeness markers, and respectful forms of address. The research employed a descriptive qualitative method, commencing with observation in different social settings in Acehnese society to identify instances of polite and impolite speech. The data for this study consists of oral data obtained from 13 informants residing in North Aceh, Aceh Pidie, Aceh Besar, and South West Aceh. Data were collected using direct observation techniques and free recall techniques. To ensure well-documented data collection, the researcher recorded the data in manual notes and electronic recordings. Data analysis was conducted using contextual methods. The results demonstrate that in Acehnese language, the politeness and grammaticality of an utterance are highly dependent on the region of use or dialect. Generally, in Acehnese, language is considered polite if the utterance uses proclitics corresponding to the actor in a sentence. However, in the South West Aceh dialect, this rule does not apply. In this dialect, language politeness does not rely on the regular use of proclitics. Proclitics are usually not used in speech and should be attached to the verb, given in the repetition of the subject as the doer of the action. Additionally, politeness in this language is highly dependent on pronouns. Conversely, the rules for using honorific pronouns in other dialects do not measure politeness and grammaticality.